Peran Boarding School Dalam Mengembangkan Pendidikan Karakter Peserta Didik(Studi Kasus di Asrama Baitul Hikmah MTs Negeri 1 Surakarta Tahun 2016) - Prasetyo, Irvan; , Drs. Abdullah Mahmud, M,Ag (2017)
Character education is a process conducted for strengthening and developing certain values wich so manifest in the behavior of students, either in the school or out of school. Value investment in children needs to be done continously, through habituation good behaviors in everyday life. Implementation of character education requires imitation and habituation, habituation to do good, to be honest, to helping each other, and to tolerate, because the character is not formed in an instant procces, but should be trained seriously and continuously and proportionally in order to achieve the ideal form of character. Schools labeled Islam and having the Boarding School program (hostel) usually have a complete Islamic studies curriculum. The school is a place of learning that supports the formation of character. Known as forming independent character, in the dorm the students should be trained to do all his own needs since he wake up until he sleep again. The problem in this research is what is the role of Boarding School (hostel) Baitul Hikmah in developing character of learners. So the purpose of this study is to describe the role of Boarding School (hostel) Baitul Hikmah in developing character of learners. This research which is conducted in Dormitory Baitul Hikmah MTs Negeri 1 Surakarta is included in the field research. The object of this study are the leaders of the dormitory, the dormitory supervisors, the teaching staffs at the hostel and some related parties such as the students. In this study data collection uses interviews, observation and documentation. These results indicate that the role of boarding school in developing characters of learners, are: instilling the values of character education to the students, familiarizing the values of character education students, applying the values of character education by students, evaluate the values of character education students. Some values of character education helding in Dormitory Baitul Hikmah, are: religious, honesty, trust, discipline, self-reliance, a healthy lifestyle, confidence, and manners. And methods used in the development of character education in the hostel Baitul Hikmah are; method of habituation, an exemplary method, method of reward and punishment method. Keywords: Role Boarding School and character